2013
DOI: 10.1063/1.4775798
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of Cu ions injection into low-k nanoporous materials under oscillating applied fields

Abstract: Cu injection into low-k dielectrics was studied using oscillating bipolar field experiments coupled with a mass transport model. Cu/SiCOH/Si structures were stressed using an oscillating square bipolar applied field at 200 °C. Breakdown was defined experimentally as the time it takes for the leakage current to exceed 1 × 10−5 A under given stress conditions. Time to failure was found to depend on field oscillating frequency and amplitude of the applied field. It was determined that ion solubility primarily aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…247 Integrated requirements.-Cu/metal diffusion resistance.-An obvious integrated requirement for any dielectric diffusion barrier / metal capping layer is to prevent diffusion of the metal wire into the surrounding ILD. The presence of metal contamination in the ILD has been attributed to a number of reliability issues 248 such as increased leakage currents, [249][250][251] decreased TDDB lifetime [252][253][254][255][256][257][258] and shifts in CMOS device performance. [259][260][261][262][263][264] A number of Cu barrier performance tests have been reported in the literature.…”
Section: -122mentioning
confidence: 99%
“…247 Integrated requirements.-Cu/metal diffusion resistance.-An obvious integrated requirement for any dielectric diffusion barrier / metal capping layer is to prevent diffusion of the metal wire into the surrounding ILD. The presence of metal contamination in the ILD has been attributed to a number of reliability issues 248 such as increased leakage currents, [249][250][251] decreased TDDB lifetime [252][253][254][255][256][257][258] and shifts in CMOS device performance. [259][260][261][262][263][264] A number of Cu barrier performance tests have been reported in the literature.…”
Section: -122mentioning
confidence: 99%
“…Bipolar applied field tests were carried out to identify possible changes in ion concentration at the metal/low-k interface as a function of the O 2 plasma treatment. The concept and procedure for bipolar applied fields tests were discussed by Borja et al 13,14 Here, time to failure (TTF) is measured for samples stressed at high temperature under a bipolar applied field. The authors are able to extract the diffusivity and concentration of ionic species by combining TTF data with a mass transport model.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the lifetime enhancement observed when applying a fast alternating field is larger for 7% pristine samples than for the plasma treated films. When using the model in Borja et al, 13,14 it was found that an increase in the concentration of ionic species at the metal/SiCOH interface accounts for the lowering of TTF observed upon exposure to the O 2 plasma. Predictions from the mass transport simulation correlate well to experimental data when the ion concentration in the model at the metal/low-k interface is increased from 1.1 × 10 26 ions/m 3 to 2.9 × 10 26 ions/m 3 .…”
Section: Resultsmentioning
confidence: 99%